2018
DOI: 10.1002/etc.4188
|View full text |Cite
|
Sign up to set email alerts
|

The production and release of microcystin related to phytoplankton biodiversity and water salinity in two cyanobacteria blooming lakes

Abstract: To find the connections between microcystins and the phytoplankton community, coupled with environmental factors, we investigated 2 cyanobacteria blooming lakes, Lake Taihu (at the center of the Yangtze River Delta, eastern China) and Lake Yanghe (near Qinhuangdao City, northern China). Two years of data, including water quality and the amounts of phytoplankton, microcystins, and the congeners in both algal cells and water, were collected from the 2 lakes during 2013 and 2014. The results showed that both the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…Several environmental factors have been shown to control the MC production in cyanobacteria. Thus, microcystin production is reported to vary with salinity [91,92], temperature [93,94], light intensity [95,96], pH [97,98] and nutrients [99,100]. However, in the Itupararanga reservoir, no significant correlations between environmental variables, MC concentrations and potentially toxic genera were found.…”
Section: Microcystin and Environmental Variablesmentioning
confidence: 99%
“…Several environmental factors have been shown to control the MC production in cyanobacteria. Thus, microcystin production is reported to vary with salinity [91,92], temperature [93,94], light intensity [95,96], pH [97,98] and nutrients [99,100]. However, in the Itupararanga reservoir, no significant correlations between environmental variables, MC concentrations and potentially toxic genera were found.…”
Section: Microcystin and Environmental Variablesmentioning
confidence: 99%
“…as recommended by the World Health Organization (WHO, 2011). Numerous studies reported that microcystin production could vary with the salinity (Jia et al, 2018;Vergalli et al, 2020), temperature (Bui et al, 2018;Walls et al, 2018), light intensity (Wiedner et al, 2003;Xie et al, 2016;Wang et al, 2019), pH (Francy et al, 2016Huang et al, 2019), and nutrients . However, no significant correlations between environmental variables, MC concentrations and potentially toxic genera were found in this study.…”
Section: Environmental Variables and Cyanotoxinsmentioning
confidence: 99%